cos(5x)+cos(5y)=0

Simple and best practice solution for cos(5x)+cos(5y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for cos(5x)+cos(5y)=0 equation:


Simplifying
cos(5x) + cos(5y) = 0

Remove parenthesis around (5x)
cos * 5x + cos(5y) = 0

Reorder the terms for easier multiplication:
5cos * x + cos(5y) = 0

Multiply cos * x
5cosx + cos(5y) = 0

Remove parenthesis around (5y)
5cosx + cos * 5y = 0

Reorder the terms for easier multiplication:
5cosx + 5cos * y = 0

Multiply cos * y
5cosx + 5cosy = 0

Solving
5cosx + 5cosy = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '5cos'.
5cos(x + y) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'cos' equal to zero and attempt to solve: Simplifying cos = 0 Solving cos = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cos = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(x + y)' equal to zero and attempt to solve: Simplifying x + y = 0 Solving x + y = 0 Move all terms containing c to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + y = 0 + -1x Combine like terms: x + -1x = 0 0 + y = 0 + -1x y = 0 + -1x Remove the zero: y = -1x Add '-1y' to each side of the equation. y + -1y = -1x + -1y Combine like terms: y + -1y = 0 0 = -1x + -1y Simplifying 0 = -1x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3(x-3)=2(6+x)1/2 | | y=x(2)-2x+3 | | 2k-10-7=8 | | 5(-2x-4)=97+3(4x+5) | | logx+log(4x-3)=1 | | 13=x^2-14x | | 32w-8w+21=69 | | 9y-15=-3(y+7) | | 22590-x=17500 | | 46t-9t+7t-40t+12=96 | | T(x)=2x^2+8x+6 | | 7x+12y=1 | | 62=5x | | 6p+14q= | | 4k+k-2k+8=86 | | 25-8x=1 | | -2p+24=13 | | 5x+8=6x-21 | | 92m-62m-23m-4m-m+7=95 | | 45-14y=5+6y | | 15=-4d+3 | | 39k-21k-6k-4k-7k=42 | | 14-4y=10 | | (2+y)(5y-4)=0 | | 5a+2=-18 | | 1.25x+12y=60 | | 3=-7k+3 | | -6f+8=2 | | 21=4b-7 | | 5(2x-3)=11 | | 8k-4=4 | | 3x-10=10-x |

Equations solver categories